Pertumbuhan dan Hasil Dua Varietas Ubi Kayu pada Empat Dosis Pupuk Npk di Lahan Pasang Surut Kalimantan Selatan - Sutrisno Sutrisno; Sri Wahyuningsih (Proceedings Series on Physical & Formal Sciences, 2021)
Tidal acid land is a potential land for cassava development. However, the development of cassava in tidal land faces many obstacles, one of which is the low availability of nutrients. This study aimed to determine the effect of NPK fertilizer in increasing the growth and yield of cassava in tidal land. The experiment consisted of two factors, the first factor was two varieties of cassava and the second factor was four levels of NPK fertilizer doses. The experiment was applied in a strip plot design with variety as the horizontal factor and the level of NPK fertilizer as the vertical factor and repeated three times. The growth parameters observed consisted of plant height, stem diameter, plant biomass weight, number of large tubers, number of small tubers, large tuber length, length of small tuber, the diameter of large tuber, the diameter of small tuber, the total number of tubers, the weight of large tuber, the weight of tuber small, and total tuber weight. The results showed that fertilizer application was effective in increasing vegetative growth and yield of cassava but increasing the dose of fertilizer was not effective in increasing the growth and yield of cassava. Differences in varieties generally did not show differences in vegetative growth and some yield components but still showed different results in the components of tuber length and total tuber weight.